2015
DOI: 10.3390/ijms16012130
|View full text |Cite
|
Sign up to set email alerts
|

Running Exercise Alleviates Pain and Promotes Cell Proliferation in a Rat Model of Intervertebral Disc Degeneration

Abstract: Chronic low back pain accompanied by intervertebral disk degeneration is a common musculoskeletal disorder. Physical exercise, which is clinically recommended by international guidelines, has proven to be effective for degenerative disc disease (DDD) patients. However, the mechanism underlying the analgesic effects of physical exercise on DDD remains largely unclear. The results of the present study showed that mechanical withdrawal thresholds of bilateral hindpaw were significantly decreased beginning on day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…While sedentary inflamed rats experienced ongoing deficits in weight bearing over the three-week period, inflamed rats engaging in voluntary running exhibited a steady improvement in weight bearing capacity of the ipsilateral paw, achieving basal levels by three weeks post-CFA. In studies using forced exercise paradigms, while not all groups describe complete exercise-induced reversal of hypersensitivity to von Frey stimulation, most produce progressive improvements over spans of a few days to more than five weeks [9; 11; 1824; 35; 54; 63; 69; 82; 93; 102; 103; 112; 132]. Strikingly, development of the CFA-induced thermal hypersensitivity observed in the sedentary inflamed group was prevented by only one week of voluntary running.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While sedentary inflamed rats experienced ongoing deficits in weight bearing over the three-week period, inflamed rats engaging in voluntary running exhibited a steady improvement in weight bearing capacity of the ipsilateral paw, achieving basal levels by three weeks post-CFA. In studies using forced exercise paradigms, while not all groups describe complete exercise-induced reversal of hypersensitivity to von Frey stimulation, most produce progressive improvements over spans of a few days to more than five weeks [9; 11; 1824; 35; 54; 63; 69; 82; 93; 102; 103; 112; 132]. Strikingly, development of the CFA-induced thermal hypersensitivity observed in the sedentary inflamed group was prevented by only one week of voluntary running.…”
Section: Discussionmentioning
confidence: 99%
“…exercise initiated after injury) in human chronic pain populations are mixed, mainly due to differences in type of pain, type of exercise and exercise intensity [40; 55; 67; 72; 95]. In contrast, rodent studies employing therapeutic exercise uniformly show robust analgesic effects in a variety of persistent pain models and using a variety of exercise intensities [4; 9; 11; 1824; 34; 35; 41; 54; 63; 69; 81; 82; 93; 102; 103; 112; 132]. Importantly, none of these studies assessed stress-related outcomes such as plasma corticosterone despite employing forced running paradigms that can be highly stressful [28; 36; 48; 62; 74; 80; 88; 89; 92].…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, the vast majority of studies (36 or 90%) reported that at least some form of therapeutic exercise was effective in reducing or reversing mechanical hypersensitivity. While three of the four studies showing no beneficial effect of therapeutic exercise on mechanical hypersensitivity initiated exercise 8 or more days after injury [ 92 , 98 , 118 ], other studies using similar delays in initiation of exercise were effective [ 87 , 91 •, 114 ••, 116 , 119 , 120 ]. Similarly, while two of the four studies showing no beneficial effect of therapeutic exercise on mechanical hypersensitivity used voluntary exercise paradigms [ 98 , 101 ], other studies using voluntary exercise were effective [ 87 , 97 , 99 ••, 100 ••].…”
Section: Is Exercise Beneficial In Rodent Models Of Chronic Pain?mentioning
confidence: 99%
“…Physical exercise is clinically recommended in several guidelines to help in alleviating pain [67] Physical exercise helps in IVD cell proliferation in animal model studies, particularly in moderate to high volume low repetition and frequency exercises [68,69]. It has effect on paraspinal muscle strength and aids in reducing pain and disability [70].…”
Section: Exercisementioning
confidence: 99%